Peran Lembaga Pengawas Pemilu: Data Pemilih Berkualitas menuju Pemilu 2024 - Sultan, Zulkifli; Muhammad; Alqarni, Wais (Universitas Indo Global Mandiri, 2023)
Performance as a result of work related to organizational goals such as quality, efficiency and other effectiveness criteria, the quality of voter data is one of the goals of holding elections. The purpose of this study was to determine the extent to which the performance of election supervisors influences the improvement of the quality of voter data in the South Sulawesi Province region. The research will be carried out using a qualitative approach, namely a more in-depth approach that will result in a more comprehensive study of existing phenomena, in addition to the method of collecting data by conducting interviews with informants and sources who are in direct contact with the object of research, there are 8 informants who consisting of election supervisors (Bawaslu), technical implementers (KPU) and people who have been registered as voters. The results of this study are to show that there is a positive and significant relationship between the performance of election supervisors in carrying out their duties and responsibilities with the quality of voter data, especially in the province of South Sulawesi, even though currently the quality of voter data has not yet reached a quality value because there are still many problems left from the start. election until the completion of the election so that it takes the active role of all parties such as society and government.